Screening of cucumber varieties and hybrids for selection of downy mildew resistance sources - N. T. Amirkhanova; A. S. Rsaliyev (Вавиловский журнал генетики и селекции)
Cucumber downy mildew (causative agent – Pseudoperonospora cubensis Rostowz) is one of the most harmful diseases of cucumbers in Kazakhstan. High variability of the fungus leading to the emergence of new aggressive pathotypes and consequently to loss of resistance by some crop cultivars causes ever-growing harmfulness of P. cubensis. The goal of the research is to carry out immunological evaluation of cucumber varieties and hybrids from 18 countries to Kazakhstanean population of the fungus and to assess their resistance against the background of artificial inoculation as well as to find stable sources of crop resistance to the disease. Eighty cucumber cultivars from Kazakhstan, Uzbekistan, Tajikistan, Turkey, India, Serbia, Russia, Ukraine, USA, Moldova, Germany, Netherlands, Italy, France, Israel, China, Taiwan and South Korea were tested for their resistance to the downy mildew in the field. Synthetic population of the cucumber downy mildew agent was used for inoculation. The studies in 2015–2016 resulted in the detection of 29 (36.2 %) cucumber varieties and hybrids that demonstrated a high rate of field resistance to the pathogen. Nine (11.2 %) varieties and hybrids appeared to be resistant, three (3.8 %) were moderately resistant, three (3.8 %) were susceptible, and 36 (45.0 %) cultivars of different origin appeared to be highly susceptible. Resistant cultivars were rather frequent among materials from Kazakhstan and Netherlands. Adoption and cultivation of resistant cucumber varieties will allow reducing application of chemical protection means, producing ecologically safe farm produce and avoiding pollution of ecosystems.